Determinants of Immunization Defaulting Among Children Aged 0–5 Years in Akure North Local Government Area, Ondo State, Nigeria - Adeleke, Amin Muyiwa; Abiodun, Akintomide Adeola; Saleh, Rakiya; Tella, Adedamola; OKIJIOLA, Samuel Omobowale; Lorumbur, GUNDU; Paul, Femi Falana (American Journal of Biology and Natural Sciences, 2025)
Introduction: Immunization remains one of the most cost-effective public health interventions for reducing morbidity and mortality among children. Despite its proven benefits, many communities in Nigeria continue to experience suboptimal immunization uptake and persistent defaulting. Understanding the determinants of immunization defaulting is crucial for improving coverage and protecting children from vaccine-preventable diseases. Objective: This study investigated the socio-demographic, behavioral, and health-service related factors influencing immunization defaulting among children aged 0–5 years in Akure North Local Government Area, Ondo State, Nigeria. Method of Analysis: A descriptive cross-sectional design was employed, and data were collected using a structured questionnaire administered to mothers of children aged 0–5 years. Descriptive statistics summarized respondents’ characteristics, knowledge, and attitudes, while chi-square tests assessed associations between key variables and immunization defaulting. Results were presented in tables and interpreted according to standard academic conventions. Results: Findings showed generally high knowledge and positive attitudes toward immunization among respondents, with 96.7% reporting adherence to immunization schedules. However, 20.7% had missed at least one appointment. Significant determinants of immunization defaulting included maternal occupation (χ²=11.42, p<0.05), distance to vaccination sites (χ²=14.36, p<0.05), long waiting times (χ²=10.25, p<0.05), and vaccine stock-outs (χ²=12.17, p<0.05). Although mothers demonstrated willingness to immunize their children, systemic and logistical barriers were major contributors to defaulting. Conclusion: The study concludes that while maternal awareness and attitudes toward immunization are favorable, health-service challenges and socio-demographic constraints significantly contribute to immunization defaulting. Strengthening service delivery, improving accessibility, and implementing targeted maternal support interventions are essential to reduce defaulting and improve child immunization coverage in Akure North LGA.